Translation to the Third and Fourth Generations: The Gbaya Bible and Gbaya Language Enrichment. Issue 2 (August 2018) - Noss, Philip A.
The story of the Gbaya Bible begins with the first translation efforts of the early missionaries and the first Gbaya Christians. As the language was being standardized, the New Testament was translated and the Christian church was being planted. The second generation of translation was carried out by an interconfessional team of mother-tongue speakers who followed the principles of dynamic equivalence and Gbaya oral literary style. Shifting toward functional equivalence as they developed the language, their effort culminated in the publication of the Bible with the Deuterocanon. The third generation is represented by today's community of Gbaya theologians and scholars who build on their predecessors' use of the Gbaya language, employing it for the creation of written literature, for theological discourse, and for academic commentary. As they exploit the resourceful features of Gbaya expression, they continue to press the communicative world of the Gbaya ancestors into a future without bounds.